Analysis of Mathematical Literacy Ability Based on Learning Style of Middle School Students - Dwiyanto, Anggie Risma; Kurniasih, Meyta Dwi (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research was conducted at SMP Negeri 204 Jakarta with research subjects, namely class VIII-B students. This study aimed to determine students' mathematical literacy skills based on Kolb's learning style. The method used in this study is descriptive qualitative, using instruments like questionnaires, test questions, and interview guides. Questionnaires are used to categorize Kolb's learning styles. At the same time, the mathematical literacy test was given as many as four description questions with Circle material and interview guidelines to find more in-depth information related to the mathematical literacy abilities possessed by the subjects in this study. Based on the research that has been done, students with diverging learning styles tend to use concrete experiences they have learned and are not afraid to try. Subjects with an assimilation learning style tend to emphasize theory, subjects with a convergent learning style look more active and have high self-confidence, and accommodation subjects tend to have concrete problem-solving experiences. Subjects with the Kolb learning style can show the process of mathematical literacy, which is suitable for the context of still common questions.